AKTIVITAS KUAU RAJA (Argusianus argus Linnaeus, 1766) PADA MATING RING DI HUTAN KONSERVASI KALAWEIT SUPAYANG, SOLOK, SUMATERA BARAT - Rafi, Muhammad; Novarino, Wilson; Rizaldi, Rizaldi; Ardiyanto, Asferi (Metamorfosa: Journal of Biological Sciences, 2017)
A behavioral study of Great Argus Pheasants ( Argusianus argus Linnaeus, 1766) at their mating ring has been done from October 2015 to January 2016 in The Kalaweit Supayang Conservasion Forest, Solok, West Sumatra. The purpose of this research is to know about activities of Great Argus Pheasant and how their activities done. Field observation in the mating ring was conducted using ten video camera traps for three months at their mating ring. Those cameras were activated for 60 seconds per session by 10 seconds intersession intervals. Behavioral data were tabulated from video records using continuous recording method. There were eight activities of Great Argus Pheasant at their mating ring which divided into individual and pairmate activities. The individual activities of male included clearing, walking, vigilance, feeding, grooming, resting, and calling. While  female activities included resting, grooming, and walking. Activity with pairmate was dancing where male performed dancing only in the present of  female. Male spent 26 times longer than females appeared at the mating ring. The peak activities at mating ring was in the morning between 7:00  and 8:00 am.
Keywords: activity, Great Argus Pheasant, camera trap, mating ring